ANALISIS KINERJA PENYELENGGARAAN MAKANAN DAN TINGKAT KEPUASAN KONSUMEN RESTORAN KHAS PADANG DI BOGOR - Atikah, Nisa Sinti; Setiawan, Budi (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2014)
This research aimed to analyze food service performance and level of customer satisfaction in Etnic Padang restaurant in Bogor City. Case study design was applied in this study. Sampling method of purposive sampling was carried out and number of subjects used was 99 people. Based on Importance Performance Analysis, results showed that the most important attribute was cleanliness of dining room and the highest performance levels was safety and hygiene products. Based on Customer Satisfaction Index the satisfaction value gained was 79 (satisfied). Spearman’s correlation showed that there was relationship between income with quality of the product (p<0.05).